Targeting the Γ-Aminobutyric Acid a Receptor (gabaar) to Alleviate Inflammation for Asthma and Neuropathic Pain - (:unkn) unknown (My University, 2019)
The γ-Aminobutyric Acid A Receptor (GABAAR) is a ligand-gated, pentameric chloride channel composed of subunits that include α1-6, β1-3, γ1-3, δ, ε, π, θ, ρ1-3.1-2 The most common arrangement includes two α subunits, two β subunits, and a γ subunit.3 This receptor includes two binding sites for the endogenous ligand γ-aminobutyric acid (GABA) between the α and β subunits and a binding site between the α and γ subunit for benzodiazepines, a large family of positive allosteric modulators.4-5 Benzodiazepines are one of the most prescribed classes of pharmaceuticals to treat anxiety, insomnia, and epilepsy as well as for muscle relaxation.6-7 However, adverse effects are also associated with benzodiazepine use, including tolerance, dependence, sedation, amnesia, and severe withdrawal symptoms.6, 8 Physiological effects of these compounds corresponds to their selectivity towards GABAARs containing specific alpha subunits.8 This is also the case for non-neuronal cells as these cells express narrower subsets of GABAAR subunits.9-11 A high-throughput assay was developed using automated patch clamp and cell lines stably expressing functional GABAARs to determine subtype selectivity. To determine any adverse CNS effects of novel imidazodiazepines, the rotarod assay was employed. Traditionally, this assay has been used to detect neurological deficits caused by muscle relaxants, convulsants, and CNS depressants since the 1950’s.12 It is one of the most commonly used sensorimotor assays because of its sensitivity and reliability. After its implementation, hundreds of compounds have been screened in the recent years by members of the Arnold group. Subtype-selective imidazodiazepines without CNS effects were used to target non-neuronal cell types in an effort to alleviate inflammation in asthma and neuropathic pain (NP). Many cell types play a role in the airway inflammatory response, including T-lymphocytes, alveolar macrophages, and eosinophils.13 CD4+ T-lymphocytes14 and macrophages15 have both been shown to express GABAAR, however eosinophils have not previously been investigated.16-17 Herein, it is demonstrated that eosinophils express GABAAR subunits. The ability of imidazodiazepines to reduce inflammation was investigated by measuring the production of nitric oxide (NO) in activated macrophages. NO can cause vasodilation18, increase in mucus secretion18, recruit eosinophils18, cause cell injury and airway remodeling19, and mediate steroid resistance.19 Exhaled NO is used to determine the severity of lung inflammation of asthmatics.19 Among many compounds investigated, a novel imidazodiazepine was identified with the ability to reduce NO production. Lymphocytes mediate the inflammatory response in asthma by infiltrating the airway and secreting inflammatory mediators, such as cytokines and chemokines.20 Functional GABAAR were confirmed on lymphocytes and targeted with novel imidazodiazepines to reduce IL-2, a cytokine associated with asthma exacerbations.21 The reduction of IL-2 was accompanied by a reduction of intracellular calcium, a signaling molecule that underlies many inflammatory processes.22 Alveolar macrophages have been successfully targeted with novel imidazodiazepines.23-24 Interestingly, these cells have been reported to be developmentally related to other resident macrophages, including microglia, the resident macrophages in the central nervous system.25 Microglia have been shown to express GABAAR subunits11, however a full characterization was not completed. It is demonstrated that human and mouse microglia express functional GABAAR that can be modulated with novel imidazodiazepines. Neuropathic pain has been suggested to be caused by hyper-excitability of neurons, however new evidence showed that the underlying cause is inflammation as a result of microglial activation.26-27 Upon nerve injury, microglia are stimulated to cause an influx of intracellular calcium28-29, which leads to upregulation of numerous inflammatory mediators, including cytokines, chemokines, and cytotoxic compounds; substances known to contribute to allodynia, hyperalgesia, and nociception.30-32 Novel imidazodiazepines have been identified among many compounds that reduce NO production, a key inflammatory modulator that causes extensive cell damage.33 Further experiments showed that this reduction was caused by a decrease in intracellular calcium, which in turn downregulated transcription and translation of iNOS, the enzyme responsible for generating nitric oxide during the inflammatory response.34 Initial experiments showed that these compounds have a stronger interaction with the κ opioid receptor than with GABAAR.
Keywords: Asthma; GABA; GABAA Receptor; Imidazodiazepine; Neuropathic Pain